The Influence of High School Students' Mathematical Curiosity on Interest in STEM Learning - Maqruf, Agus; Patunah, Siti; Sumiati (International Journal of Research in Mathematics Education, 2024)
The study had explored the influence of high school students' mathematical curiosity on their interest in STEM (Science, Technology, Engineering, and Mathematics) learning. Using a quantitative approach, the study had involved 271 students from various high schools, who had filled out a questionnaire regarding their level of mathematical curiosity and interest in STEM learning. Regression analysis had been conducted to identify the relationship between the two variables. The study's results had revealed a significant relationship between mathematical curiosity and interest in STEM learning, with a p-value of <0.05. This finding had indicated that students' mathematical curiosity had simultaneously influenced students' interest in STEM learning with several indicators that had significantly affected interest in STEM learning, namely the desire to detail information and enthusiasm for learning. The implications of these results had highlighted the importance of designing teaching strategies that could trigger students' mathematical curiosity to increase their engagement in STEM fields.